Characterization of Lactic Acid Bacteria (LAB) from Tempeh Probiotic Drink with Combination of Dates and Skim Milk - Aýun, Qurrota; Muthiáh, Sari Niswatul; Tiara Perdana , Analekta (Konservasi Hayati, 2024)
Tempeh can be processed into a probiotic drink because it contains Lactic Acid Bacteria (LAB), which are beneficial for the digestive system. A combination of dates and skim milk as prebiotics is required by LAB as a substrate to produce energy and cellular components, and to increase the population to produce sufficient amounts of acid. This study aims to describe the characteristics of LAB present in tempeh probiotic drinks with a combination of dates and skim milk. Isolation was performed using the total plate count (TPC) method with the spread plate technique. Selected isolates were identified macroscopically, microscopically, biochemically, and physiologically. The results showed that the average amount of LAB viable counts was 9.6 x 106 CFU/mL with 8 suspected isolates as LAB. Microscopic observation obtained all 8 isolates were Gram-positive with two round shapes and six-rod shapes. The catalase test results showed all 8 isolates were negative due to the absence of bubbles. The triple sugar iron agar (TSIA) test showed a yellow color, indicating the capability to ferment glucose, lactose, and sucrose. All selected isolates non-motile and positive MR and negative SCA testing. Some of the isolates showed tolerance to salts and acids based on physiological testing. The six most promising LAB isolates showed important characteristics of LAB that should be evaluated when selecting probiotic candidates, namely TEa-4130, TEb-4230, TEb-4130, TEb-3150, TEb-3250, and TEb-4250 isolates.